A REFLECTIVE APPROACH FOR TEACHING SEMI-AUTOMATIC TRANSLATION PRACTICE IN TRANSLATOR TRAINING PROGRAMS - Andrade Stupiello, Erika Nogueira de [UNESP] (Univ Federal Santa Catarina, Nucleo Traducao, 2019)
Translation memory systems have been promoting definitive changes in the development and contracting criteria of translations of texts in electronic format. With the purpose of examining the influence of the use of these tools in the production of translators in training, this paper presents a study proposing a reflective approach for the analysis of translations by students in academic training. For this purpose, eight participants attending the third year of an undergraduate program in Translation were invited to translate three contracts from English into Brazilian Portuguese with and without the assistance of Wordfast Classic (version 6.0). The results of the analysis of the students' translations suggest that those who used the tool produced more uniform translations, with high similarity index between them, which may be indicative of the influence of the memory in the translation work. In view of the scarce research focused on the analysis of the way translators interact with the tools employed in their work and how they are affected by them, this study aims to contribute to a better understanding of the possible implications involved in the association between the translator and translation memory systems in the work of translation.
Keywords: Translation memory systems; Turnitin; Translator training; Technology